Ontogenetic development of chaetotaxy in Tenuipalpidae: a survey with special reference to sexual dimorphism - Gu, Xin-Yao; Zhang, Zhi-Qiang (Zootaxa, 2020)
In this paper, we provide a comparative survey of ontogenetic development of chaetotaxy in the family Tenuipalpidae, with the aim to compare patterns among species/genera and to discover some general trends. We also want to find gaps within published literature and provide suggestions for future studies. Although we focused on the ontogeny of setal developments, we also reviewed sexual dimorphism in chaetotaxy in the family Tenuipalpidae.